Displaced osteochondral fracture of the posterolateral tibial plateau associated with an acute anterior cruciate ligament injury - de Andrade, Marco Antônio Percope (Trauma Case Rep, 2019)
An osteochondral fracture of the posterolateral tibial plateau associated with an anterior cruciate ligament (ACL) injury in a 24-year-old boy is reported. Anterior cruciate ligament rupture is accompanied by bone contusions resulting from the impact of the posterolateral tibial plateau on the anterior part of the lateral femoral condyle. The osteochondral fracture of the posterolateral tibial plateau matched the site where the bone bruise is observed.